Tracing the Heat: LULC Changes and Urban Heat Island Dynamics in Abu Dhabi's Expanding Landscape - B. Dahy; Y. Yin; P. Marpu; C. B. Nixon; R. Sousa (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
Urban Heat Island (UHI) effects in arid environments are influenced by urban expansion, land-use changes, and water body dynamics. This study provides an updated analysis of UHI trends in Abu Dhabi using Land Surface Temperature (LST) data retrieved from moderate-resolution Landsat imagery spanning from April 2013 to December 2024. Monthly and seasonal LST trends are assessed across four land-use categories: consistent urban, land to urban (developed), inundation, and reclamation. Results reveal that while urban areas exhibit a cooling trend in peak summer (−2.46°C/year), they show a significant warming trend in winter (+2.64°C/year), reinforcing UHI effects. Inundation zones demonstrate the oasis effect, mitigating peak summer heat (−2.37°C/year). At the same time, reclamation areas show sustained warming in both seasons (+2.93°C/year in summer, +4.20°C/year in winter), indicating the loss of natural heat-buffering mechanisms. A key novelty of this study is the integration of land cover and land-use change analysis with multi-seasonal LST trends, revealing the aggressive construction-driven transformation of the urban landscape. Unlike previous studies (e.g., Lazzarini et al., 2015), which primarily documented UHI presence, our research highlights how changes in land-use composition, particularly the loss of water bodies and green spaces due to reclamation, exacerbate warming trends despite urban cooling interventions. The findings challenge earlier assumptions of a uniform UHI increase, showing that land-use planning plays a decisive role in seasonal heat retention and dissipation. However, ongoing land reclamation appears to counteract these gains, necessitating further research on climate adaptation strategies.